Penanganan Limbah Organik Pada Tambak Untuk Memperbaiki Kualitas Tanah Dasar Tambak - Basuki Setiyo Budi (Politeknik Negeri Semarang, 2015)
Pond development a river embankment Samtren Mangunharjo Tugu Semarang is done without regard to the technical prerequisites such as irrigation systems, supply and exhaust channels, broad expanse of the maximum, planning, design, layout and construction of ponds that are less coordinated, and without management contaminant causing environmental degradation Mangunharjo region, which in turn lowers the productivity of the pond. The purpose of this study is to examine the fundamental characteristics of organic matter on the pond bottom soil by using micro-organisms. Contact time and the process by utilizing micro-organisms is the novelty of this study. Provision of organic waste is influenced by two factors, the first factor is the large concentration of micro-organisms that function as decomposers of organic waste and controlling selectivity allowance to degrade organic waste. The second factor is the contact time is the period average - Average required to react with the organic waste in the soil microbial pond. To gain a comprehensive understanding of the process, this research is focused on reduction of process parameters by utilizing micro-organisms and the contact time and concentration of organic waste. While the technical aspects paralleled through laboratory experiments, theoretical models and pilot-scale test in the pond. Characteristics of the allowance system is analyzed based on the rate of elimination of organic waste organic wastes, contact time and concentration of micro-organisms. Evaluation was also conducted to determine the feasibility and advantages of technology and commercial applications. Research conducted laboratory scale then performed preliminary studies with varying characteristics of process parameters of micro-organism concentration, contact time, developed a management model and the characteristics of the organic waste to the pond bottom soil management and techno-economic evaluation. This study provides measurable outcomes such as: (i) management models and characterization of organic waste in the pond bottom soil in coastal environmental management of the effort. (ii) Product pond bottom soil management technologies. (iii) scientific publications in journals.